PEMANFAATAN KECERDASAN BUATAN(AI) DALAM PEMBELAJARAN : PERSPEKTIF PENDIDIK DAN TANTANGAN IMPLEMENTASI - Erika Dwi Paramita; Ayu Maya Damayanti; Meidiana Aulia Pratiwi; Nugroho Dwi Yulianto; Noviana Bella Donna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine teachers’ experiences in utilizing artificial intelligence (AI) as part of classroom learning. The rapid development of AI technology offers opportunities for instructional innovation while simultaneously presenting challenges for educators, particularly in pedagogical practices, assessment, and classroom management. This study employs a qualitative approach using a literature review method through a systematic examination of relevant scholarly sources. Data were analyzed using content analysis techniques to identify key themes related to the use of AI, perceived benefits, implementation challenges, and pedagogical implications. The findings indicate that AI has the potential to enhance learning personalization, improve instructional efficiency, and support teachers in assessment and administrative tasks. However, the integration of AI remains constrained by limitations in teachers’ digital competencies, infrastructure readiness, and ethical concerns. Therefore, institutional support, continuous professional development, and a clear pedagogical framework are essential to ensure the effective and responsible use of AI in education.